Neuroprotective effects of human umbilical cord mesenchymal stromal cells in an immunocompetent animal model of Parkinson's disease - Mathieu, Patricia Andrea (2012)
Microglial activation in the substantia nigra (SN) is a ubiquitous feature in PD which could mediate toxic effects. Human mesenchymal stromal cells (hMSCs) possess immunomodulatory properties. We evaluated whether the transplantation of hMSCs obtained from umbilical cord had a neuroprotective effect in a not-immunosuppressed rat Parkinson's disease (PD) model. Rats receiving hMSCs in the SN displayed significant preservation in the number of dopaminergic neurons in the SN at 21. days after lesion and an improved performance in behavioral tests compared to control rats. However, no differences in any inflammatory parameter tested were found. These results suggest that grafted hMSCs exert neuroprotection but not neuromodulatory effects on degenerating dopaminergic neurons.